DEVELOPMENT COMMUNICATION AS AN EASY-TO-UNDERSTAND LANGUAGE IN THE VILLAGE DEVELOPMENT PROGRAM OF KOTA RANTANG HAMPARAN PERAK DELI SERDANG NORTH SUMATRA - Hasibuan, Nabila Afifaturraihana; Dayana (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
Development communication is one of the breakthroughs in the social sciences, that development communication for ideas and concepts is not easy to understand until it is translated into action The communication convergence referred to in this study is to see how the realities occurring during the communication process take place between the village government and the community in the development program. Convergent communication in this study has several indicators: perceiving, understanding and trusting development communication acts as a bridge for the people of Kota Rantang Village to understand the village development program delivered using easy-to-understand language so that it can be understood so that the village development program is delivered evenly. This research method uses correlation with a quantitative approach. The population in this study amounted to 6,145 people consisting of 7 hamlets in Kota Rantang Village with 1,748 heads of families using the Taro Yamane formula, the sample in this study amounted to 99 people. The results show that 51% are in the category of being able to deliver village development programs. The community can understand from difficult messages to communicative language with a percentage of 60%. The development program can be understood by the community with a percentage of 57%. The results show that the message is delivered evenly with a percentage of 67%. The community is interested in providing responses and involvement in the development program delivered with a percentage of 42%.